2020
DOI: 10.1016/j.jtauto.2020.100058
|View full text |Cite
|
Sign up to set email alerts
|

Familial risks between Graves disease and Hashimoto thyroiditis and other autoimmune diseases in the population of Sweden

Abstract: Genetic and family studies have indicated that Graves disease and Hashimoto thyroiditis have a heritable component which appears to be shared to some extend also with some other autoimmune diseases (AIDs). In the present nation-wide study we describe familial risk for Graves disease and Hashimoto thyroiditis identified from the Swedish Hospital Discharge Register (years 1964 through 2012) and the Outpatient Register (2001 through 2012). Family relationships were obtained from the Multigeneration Register and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…Disease associations with HT may shed further light on pathogenesis. A comprehensive study of over 25,000 offspring of HT patients has confirmed familial associations among 20 of 43 other autoimmune disorders, 6 of which (autoimmune haemolytic anaemia, chronic rheumatic heart disease, chronic glomerulonephritis, immune thrombocytopenic purpura, pemphigus and Takayasu disease) were not found in a similar cohort of Graves’ patients [ 44 ]. In addition modest spouse correlation was found within the overall familial risk, indicating some sharing of environmental risk factors, but the overwhelming risk was genetic and shared with other autoimmune disorders.…”
Section: Associations With Htmentioning
confidence: 99%
“…Disease associations with HT may shed further light on pathogenesis. A comprehensive study of over 25,000 offspring of HT patients has confirmed familial associations among 20 of 43 other autoimmune disorders, 6 of which (autoimmune haemolytic anaemia, chronic rheumatic heart disease, chronic glomerulonephritis, immune thrombocytopenic purpura, pemphigus and Takayasu disease) were not found in a similar cohort of Graves’ patients [ 44 ]. In addition modest spouse correlation was found within the overall familial risk, indicating some sharing of environmental risk factors, but the overwhelming risk was genetic and shared with other autoimmune disorders.…”
Section: Associations With Htmentioning
confidence: 99%
“… 39 Thyroid autoimmune diseases are the most common type of autoimmune diseases in Sweden, accounting for over 10% of all such diseases. 40 Hashimoto disease/hypothyroidism is the most common thyroid autoimmune disease and it is associated with a high risk of HCC; 12 however, whether thyroid autoimmunity is a precursor of thyroid cancer is somewhat disputed. 41 , 42 Thus there may yet be other reasons; liver cancer is marginally increased in families of patients with non-medullary thyroid cancer but no associated genes have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The study populations were younger than the present one and the familial risks tended to be higher than the current ones. In our recent analysis of thyroid AIDs, we showed that Graves disease and Hashimoto thyroiditis were associated with PA with SIRs of 1.94 and 1.74, respectively; the PA population was younger than the present one [ 23 ]. The present results and the older studies show familial risks between PA and such common AIDs which present as comorbidities in the same individuals and which probably indicate underlying genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%